Binge-Watching: Development and Validation of the Binge-Watching Addiction Questionnaire - Giuseppe Forte; Francesca Favieri; Domenico Tedeschi; Maria Casagrande (Behavioral Sciences, 2021)
The approach to the vision of TV series has deeply changed in the last years, and watching multiple episodes of TV content in a single session becomes a popular viewing pattern referred as binge-watching. Early studies defined binge-watching as a potentially addictive behavior showing characteristics similar to other behavioral addictions, such as loss of control and pleasure anticipation. This study aims to validate a short self-report questionnaire focused on assessing binge-watching behavior and determining whether it shows characteristics similar to addictive behavior, the Binge-Watching Addiction Questionnaire (BWAQ). An online survey was adopted to administer the questionnaire in the general population (N = 1277). Exploratory and confirmatory factor analyses assessed both the validity and the structure of the scale in two independent samples. The statistical analyses confirmed a four-factor model (i.e., “Craving”, “Dependency”, “Anticipation”, “Avoidance”) of the BWAQ with good psychometric properties. The BWAQ can differentiate between people who adopt maladaptive watching activities from those who use TV-series as leisure and entertainment activities. Therefore, this questionnaire may enable researchers to improve this emerging field of research significantly.